THE REPRESENTATION OF JOKO WIDODO IN THE JAKARTA POST'S ARTICLE: A CRITICAL DISCOURSE ANALYSIS - Hiras Josep; Asidiky Asidiky; R. Vindy Melliany Puspa (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
This study revealed the representation of Joko Widodo as one of the presidential candidates in the 2019 Indonesian presidential election in one of the The Jakarta Post's articles. The data was one of The Jakarta Post's articles entitled 'Jokowi accuses Prabowo's team for enlisting foreign consultant'. The theories used in this study were Halliday and Matthiessen's Transitivity (2014) and Fairclough's three Dimension of Critical Discourse Analysis model. The findings have shown positive representations of Joko Widodo. The representations can be seen from the processes used imbued in newspaper discourse. Furthermore, this positive representation can influence voters to determine the selection in the presidential election.